Pursuit - Robards, Karen (G.P. Putnam's Sons, 2009)
After rookie lawyer Jessica Monaghan meets with the First Lady, the VIP is killed in a car accident in which Jessica manages to survive. When she suspects the accident was something else and she becomes the next target, she and experienced FBI agent Mark Ryan team up to uncover the plot behind the First Lady's murder.